2017
DOI: 10.1115/1.4035841
|View full text |Cite
|
Sign up to set email alerts
|

Method for the Preliminary Fluid Dynamic Design of High-Temperature Mini-Organic Rankine Cycle Turbines

Abstract: Widespread adoption of renewable energy technologies will arguably benefit from the availability of economically viable distributed thermal power conversion systems. For this reason, considerable efforts have been dedicated in recent years to R&D over mini-organic Rankine cycle (ORC) power plants, thus with a power capacity approximately in the 3–50 kW range. The application of these systems for waste heat recovery from diesel engines of long-haul trucks stands out because of the possibility of achieving e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…Specifically, Macchi and Perdichizzi [3] showed that the optimal design (maximum efficiency) of axial turbines depends on the amount of kinetic energy that can be recovered from the last stage. In addition, the work of Bahamonde et al [4] indicates that the discharge kinetic energy can be one of the main mechanisms of efficiency loss when the influence of the diffuser is not accounted during the preliminary design. Despite this, the impact of the diffuser on the overall performance of turbomachines is often neglected or modeled in a very simple way during the preliminary design (mean-line models).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Macchi and Perdichizzi [3] showed that the optimal design (maximum efficiency) of axial turbines depends on the amount of kinetic energy that can be recovered from the last stage. In addition, the work of Bahamonde et al [4] indicates that the discharge kinetic energy can be one of the main mechanisms of efficiency loss when the influence of the diffuser is not accounted during the preliminary design. Despite this, the impact of the diffuser on the overall performance of turbomachines is often neglected or modeled in a very simple way during the preliminary design (mean-line models).…”
Section: Introductionmentioning
confidence: 99%
“…[6]. These models have been developed for conventional turbomachinery operating with fluids in the ideal gas state, and featuring subsonic flows and large Reynolds numbers.…”
Section: Methodsmentioning
confidence: 99%
“…A meanline code for the preliminary design of turbomachinery [6,26] is coupled with the in-house computational fluid library [21] in which fluid model (5) has been implemented. Among various inputs, the design model requires the turbine rotational speed X, the rotor inlet diameter D 2 , and the mass flow _ m. The successful application of the active subspaces method requires that the mathematical model is continuous and differentiable, therefore X; D 2 and _ m must be normalized, such that the input parameters are fluid independent.…”
Section: Normalized Input Of the Turbine Model For Preliminary Designmentioning
confidence: 99%
See 2 more Smart Citations